Intrauterine Foetal Death: A Hospital Based Study - Jahan, Kamar; Mahaseth, Binod Kumar (Journal of Nepalgunj Medical College, 2022)
Introduction: Foetal death at any stage of pregnancy is not just a tragic event but also a more traumatic for the mental well-being of a mother. It is one of the most wrenching events in the field of obstetrics. Aims: The study was done to determine the probable risk factors of intrauterine foetal death and role of antenatal care in its prevention. Methods: The study was conducted in Obstetrics and Gynecology department at Nepalgunj Medical college from July 2018 to July 2020 .Inclusion criteria were intrauterine fetal death of >28 weeks of gestation and baby weighing 1000 grams or more . An exclusion criterion was molar pregnancy. Results: There were 115(3.52%) intrauterine fetal death during the study period, making it 35 per 1000 cases. In 17(14.78%) the cause of intrauterine fetal death was not known. The other common associated risk factors were prematurity in 14(12.17%) and hypertension in 13(11.30%). Similarly anemia and antepartum hemorrhage were seen in 13(11.30%) each. 11(9.56%) patients had oligohydramnios. Mal presentation was found in 8(6.95%) patients while polyhydromnios in 6(5.21%).The commonest age range in whom intrauterine fetal death was seen was 20-30 (73.90%). 28 (24.34%) patients were at preterm pregnancy ranging between 28-30 weeks whereas 17(14.78) intrauterine fetal death occured at 32-34 weeks. 77 foetuses were preterm and their birth weight was between 1 - 1.5 kg with the mean wt of 1175.73 gms. Conclusion: Intrauterine fetal death is still common inspite of the improving awareness in importance of regular antenatal care. In majority, the cause of intrauterine fetal death is still unknown. However, where the cause was known prematurity was the commonest.